2012
DOI: 10.1111/j.1755-3768.2012.02533.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of amphoteric rinsing solution for treatment of ocular tissues exposed to nitrogen mustard

Abstract: ABSTRACT.Purpose: Ocular exposure to mustard agents may cause severe and prolonged injury to the anterior segment tissues. Effective decontamination of the external eye surface after exposure is of paramount importance. The purpose of the present study was to assess the effectiveness of Diphoterine rinsing solution (DRS) in reducing ocular damage after exposure to nitrogen mustard (NM) and to compare it with normal saline solution. Methods: One eye of 16 New Zealand albino rabbits was exposed to 2% NM. Immed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…On day-14, SM-exposed corneas had persistent epithelial damage, reduced corneal thickness, the repopulation of keratocyte-like cells in the stroma, and a mild recovery in the characteristic collagen fibril architecture in the stroma. These changes are consistent with previous in vivo rabbit studies 50,74,[245][246][247] . However, on day-14 TED treatment to SM exposed eye (SM+TED) restored the epithelium, corneal thickness, stromal content, and collagen architecture like a naïve cornea.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…On day-14, SM-exposed corneas had persistent epithelial damage, reduced corneal thickness, the repopulation of keratocyte-like cells in the stroma, and a mild recovery in the characteristic collagen fibril architecture in the stroma. These changes are consistent with previous in vivo rabbit studies 50,74,[245][246][247] . However, on day-14 TED treatment to SM exposed eye (SM+TED) restored the epithelium, corneal thickness, stromal content, and collagen architecture like a naïve cornea.…”
Section: Discussionsupporting
confidence: 93%
“…6,8,13,20,38 Amphoteric rinsing solutions and doxycycline hydrogels exhibit moderate clinical benefits. 50,51 Several studies have shown that the clinical utility of a steroid-based therapy (like doxycycline) is limited by the therapy's duration with a recurrence of clinical signs following the withdrawal of the steroid. 43,52,53 In addition, steroid use in patients can cause severe side effects, including glaucoma.…”
Section: Clinical Management Of Mustard Gas Keratopathymentioning
confidence: 99%
“…15 Interestingly, a recent in vivo study of rinsing with Diphoterine solution found it to be significantly more effective than saline solution in the treatment of mustard ocular injuries. 25 The main limitation of the presented study is the lack of a control group using water for cutaneous and ocular decontamination after CS exposure. As has already been presented, the police officers refused to use prepared 200 ml low-pressure container sprays filled with water for decontamination after CS exposure due to their previous bad experience with water rinsing.…”
Section: Discussionmentioning
confidence: 98%
“…15 Interestingly, a recent in vivo study of rinsing with Diphoterine solution found it to be significantly more effective than saline solution in the treatment of mustard ocular injuries. 25…”
Section: Discussionmentioning
confidence: 99%
“…If only tap water is available, it should be used immediately but there is the risk of corneal swelling. The dilution of the chemical substance by tap water will reduce pain until a more suitable eye lotion is available, but rinsing as soon as possible is of utmost importance [113,114].…”
Section: Hypertonic Eye Lotions To Prevent Oedemamentioning
confidence: 99%